MEDICAL BOARD AND MEDICAL TRAINING - Elena M. Smirnova (Высшее образование в России, 2016)
The article deals with the participation of the provincial health authorities - the medical board in organization of medical training. In Russia at the end of XVIII - early XIX cent., when regulatory framework of medical education evolved, no clear rules for admissionto educational institutions, common standards of qualification examinations existed. There were serious difficulties in recruiting medical faculties. The acute shortage of doctors forced the government to resort to administrative measures of recruiting medical and pharmaceutical personnel from among seminary students who had an acceptable level of general education, and went to meet the desire of “health officials” to improve their professional status, facilitating the passage of qualification tests. Medical boards played a role of important tools of this policy.